MiRNA‐122‐5p in POI ovarian‐derived exosomes promotes granulosa cell apoptosis by regulating BCL9. (1st March 2022) - Zhang, Xiujuan; Zhang, Ruihong; Hao, Jing; Huang, Xiaoyan; Liu, Ming; Lv, Mengxiao; Su, Chan; Mu, Yu‐Lan
Abstract: This study is to explore the therapeutic effect and potential mechanisms of exosomal microRNAs (miRNAs) derived from the ovaries with primary ovarian insufficiency (POI). The POI mouse model was established by intraperitoneal injection of cyclophosphamide (CTX) and busulfan. The apoptosis of granulosa cells (GCs) incubated with exosomes extracted from ovarian tissues of control and POI groups was analyzed by flow cytometry. Then, high‐throughput sequencing was performed to detect the difference of miRNAs profile in ovarian tissue‐derived exosomes between the control and POI mice. The effect of differential miRNA on the apoptosis of CTX‐induced ovarian GCs was analyzed by flow cytometry. The results showed that POI mouse model was successfully established. Exosomes extracted from ovarian of normal and POI group have different effects on apoptosis of GCs induced by CTX. miRNA‐seq found that exosomal miR‐122‐5p in POI group increased significantly. miR‐122‐5p as the dominant miRNA targeting BCL9 was significantly upregulated in ovarian tissues of chemotherapy‐induced POI group. Exosomes derived from the ovaries in the control group and miR‐122‐5p inhibitor group attenuated the apoptosis of primary cultured ovarian GCs. In conclusion, exosomal miR‐122‐5p promoted the apoptosis of ovarian GCs by targeting BCL9, suggested that miR‐122‐5p may function as a potential target to restore ovarian function. Abstract : This study is to explore the therapeutic effect and potential mechanisms of exosomal microRNAs (miRNAs) derived from ovarian on primary ovarian insufficiency (POI). The POI mouse model was established by intraperitoneal injection of cyclophosphamide (CTX) and busulfan. The apoptosis of granulosa cells (GCs) incubated with exosomes extracted from ovarian tissues of control and POI groups were analyzed by flow cytometry. Then, high‐throughput sequencing was performed to detect the difference of miRNA profile in ovarian tissue‐derived exosomes between the control and POI mice. Further analyzed the effect of miR‐122‐5p on the apoptosis of CTX‐induced ovarian GCs by flow cytometry. The POI mouse model was successfully established. Exosomes extracted from ovarian of normal and POI group have different effects on apoptosis of GCs induced by CTX. miRNA‐seq found that miR‐122‐5p in POI group increased significantly. miR‐122‐5p as the dominant miRNA targeting BCL9 was significantly upregulated in ovarian tissues of chemotherapy‐induced POI group. Exosome derived from the ovarian in the normal group and miR‐122‐5p inhibitor inhibited the apoptosis of primary cultured ovarian GCs. In conclusion, exosomal miR‐122‐5p promoted the apoptosis of ovarian GCs by targeting BCL9, suggested that miR‐122‐5p may function as a potential target to restore ovarian function.